Passivation layers for nanostructured photoanodes: ultra-thin oxides on InGaN nanowires. Issue 2 (13th December 2017) - Neuderth, P.; Hille, P.; Schörmann, J.; Frank, A.; Reitz, C.; Martí-Sánchez, S.; Mata, M. de la; Coll, M.; Arbiol, J.; Marschall, R.; Eickhoff, M.
Abstract : An experimental strategy to assess the influence of ultra-thin oxide coatings on the performance of InGaN nanowire photoanodes is demonstrated. Abstract : An experimental strategy for systematically assessing the influence of surface passivation layers on the photocatalytic properties of nanowire photoanodes by combining photocurrent analysis, photoluminescence spectroscopy and high resolution transmission electron microscopy with a systematic variation of sample structure and the surrounding electrolyte is demonstrated. Following this approach we can separate the impact on recombination and transport processes of photogenerated carriers. We apply this strategy to analyze the influence of ultra-thin TiO2, CeO2 and Al2 O3 coatings deposited by atomic layer deposition on the photoelectrochemical performance of In x Ga1− x N/GaN nanowire (NW) photoelectrodes. The passivation of surface states results in an increase of the anodic photocurrent (PC) by a factor of 2.5 for the deposition of 5 nm TiO2 . In contrast, the PC is reduced for CeO2 - and Al2 O3 -coated NWs due to enhanced defect recombination in the passivation layer or increased band discontinuities. Furthermore, photoelectrochemical oxidation of the In x Ga1− x N/GaN NW photoelectrode is attenuated by the TiO2 layer and completely suppressed for a layer thickness of 7 nm or more. Due to efficient charge transfer from the In x Ga1− x N NW core a stable TiO2 -covered photoanode with visible light excitation is realized.